Analysis of the Need for Pizzaluv-Math Learning Media So that Students Can Easily Learn the Limits of Trigonometric Functions - Rani Darmayanti; Akhsanul In'am; Ani Afifah; Anindita Verliana Ridho'i; Dewi Nurmaltasari (CV. Bimbimbingan Belajar Assyfa, 2023)
This research aims to analyze the need for innovative project-based learning media, namely